PENGEMBANGAN MEDIA LITERASI BIG BOOK UNTUK MENINGKATKAN KETERAMPILAN MEMBACA PEMAHAMAN SISWA SEKOLAH DASAR - Gio Mohamad Johan; Dyoty Auliya Vilda Ghasya (Program Studi Pendidikan Guru Sekolah Dasar, 2018)
This study aims to determine the validity of Big Book media literacy, the practicality of Big Book media literacy and the effectiveness of Big Book media literacy to improve reading comprehension skills of elementary school students. The type of research is a type of development research or also known as Research and Development (R & D). Development of Big Book media literacy to improve students' reading comprehension skills in elementary schools to adapt the Four D Model design. The results of this study are (1) the validity of the Big Book media based on the results of validation data by experts that the Big Book media literacy obtained a final score of 3.87 with very good criteria, (2) practicality of Big Book media was shown based on activity observation data students and teachers when using Big Book literacy media, on the observation data of student activity shows that the average score of all student activities shows good results, because all grades> 2.5 and are evenly distributed to all students, while activity observation data The teacher showed that the achievement of teacher activity scores was very good, this was evidenced by the increasing value obtained for each learner, (3) the effectiveness of Big Book media literacy indicated by the students' reading comprehension test data obtained the tcount of the pre value test of comprehension reading skills test and the post reading comprehension skill test is 4.83 den bro, the specified table is 2.04. Then the result of tcount> t table shows 4.83> 2.04. So it can be concluded that the results of the value of the test post of students' reading comprehension skills after attending the process of learning activities using Big Book media literacy increased. Abstrak Penelitian ini bertujuan untuk mengetahui kevalidan media literasi Big Book, kepraktisan media literasi Big Book dan keefektivan media literasi Big Book untuk meningkatkan keterampilan membaca pemahaman siswa sekolah dasar. Adapun jenis penelitian ini merupakan jenis penelitian pengembangan atau dikenal juga dengan Research and Development (R&D). Pengembangan media literasi Big Book untuk meningkatkan keterampilan membaca pemahaman siswa di sekolah dasar mengadaptasi desain Four D Model. Adapun hasil dari penelitian ini adalah (1) kevalidan media Big Book berdasarkan data hasil validasi oleh para ahli bahwa media literasi Big Book memperoleh nilai akhir sebesar 3,87 dengan kriteria sangat baik, (2) kepraktisan media literasi Big Book ditunjukkan berdasarkan data observasi aktivitas siswa dan guru pada saat menggunakan media literasi Big Book, pada data hasil observasi aktivitas siswa menunjukkan bahwa pemerolehan rata-rata nilai semua aktivitas siswa menunjukkan hasil yang baik, karena semua nilai >2,5 dan merata pada semua siswa, sedangkan data hasil observasi aktivitas guru menunjukkan bahwa pencapaian nilai hasil aktivitas guru sangat baik, hal tersebut dibuktikan dengan pemerolehan nilai yang terus meningkat pada setiap pembelajaranya, (3) keefektivan media literasi Big Book ditunjukkan dengan data hasil tes membaca pemahaman siswa diperoleh nilai thitung uji nilai pre tes keterampilan membaca pemahaman dan pos tes keterampilan membaca pemahaman sebesar 4,83 dengan ttabel yang telah ditentukan sebesar 2.04. Maka hasil nilai thitung>ttabel menunjukkan 4,83>2,04. Sehingga dapat disimpulkan bahwa hasil nilai pos tes keterampilan membaca pemahaman siswa setelah mengikuti proses kegiatan belajar menggunakan media literasi Big Book meningkat. Kata Kunci: Big book, keterampilan membaca pemahaman, siswa